2021
DOI: 10.3390/technologies9040071
|View full text |Cite
|
Sign up to set email alerts
|

Shape-Memory Properties of 3D Printed Cubes from Diverse PLA Materials with Different Post-Treatments

Abstract: Poly(lactic acid) (PLA) belongs to the 3D printable materials which show shape-memory properties, i.e., which can recover their original shape after a deformation if they are heated above the glass transition temperature. This makes PLA quite an interesting material for diverse applications, such as bumpers, safety equipment for sports, etc. After investigating the influence of the infill design and degree, as well as the pressure orientation on the recovery properties of 3D printed PLA cubes in previous studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 34 publications
(67 reference statements)
1
7
0
Order By: Relevance
“…However, this treatment softened the PLA scaffold and made it more flexible. Eventually, the filter became degraded and unable to retain its shape, which is consistent with the results reported elsewhere [ 21 , 38 ]. On the other hand, a diluted acetone solution with a concentration lower than 90% (wt.% in water) was not effective for GO doping compared to the case of 95 wt.% of acetone, as shown in Figure 2 b.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…However, this treatment softened the PLA scaffold and made it more flexible. Eventually, the filter became degraded and unable to retain its shape, which is consistent with the results reported elsewhere [ 21 , 38 ]. On the other hand, a diluted acetone solution with a concentration lower than 90% (wt.% in water) was not effective for GO doping compared to the case of 95 wt.% of acetone, as shown in Figure 2 b.…”
Section: Resultssupporting
confidence: 92%
“…Fused deposition modeling (FDM) is a commonly used printing method in which thermoplastic materials are heated and injected. Polyamide (PA), polycarbonate (PC), polylactic acid (PLA), polyetheretherketone (PEEK), and polystyrene (PS) are among the thermoplastic materials that are commonly used in 3D printing [ 21 , 22 , 23 ]. However, the listed thermoplastic materials do not intrinsically possess the properties required to adsorb certain types of water pollutants.…”
Section: Introductionmentioning
confidence: 99%
“…Ehrmann et al [ 21 ] explored the post-heat treatment process for PLA material for different grades and colors of PLA. The reported results suggested that there are contradictions and low reproducibility of the results with the previously reported data.…”
Section: Introductionmentioning
confidence: 99%
“…1730 ∼ 1700 cm À1 was the hydrogen-bonded urethane groups (amide I), the peak at 1072 cm À1 belonged to C-O-C stretching. 28,29 For PLA, 2996 cm À1 and 2946 cm À1 were assigned to the stretching modes of asymmetric and symmetrical C-H bonds, respectively. The stretching vibration of the C = O bond peak located at 1755 cm À1 , and 1182 cm À1 corresponds to the stretching of the ether bond.…”
Section: Ftir Measurementmentioning
confidence: 99%